A DESCRIPTIVE ANALYSIS OF THE AVIATION REGISTERS OF “SUKHOI AIRCRAFT CRASH’S NEWS” IN THE DETIKNEWS ONLINE - Suswanto Ismadi Megah (Universitas Riau Kepulauan, 2012)
Recently, people communicate by using a language but spekaer of the same langauge mostly do not understand each others if they speak by using their own ‘community language’ which was used in specific area, such as aviation. After happening of tragedy of Sukhoi Super Jet 100 crashed in West Java, Indonesian media brodcasted frequently. Journalists reported the news by using aviation terms which were very difficult for mostly people who do not understand the regsiter of aviation. Therefore, this study focuses on the regsiter used in Detiknews.online